Analisis Penetapan Harga Jual Pembiayaan Murabahah pada Lembaga Keuangan Syariah Bank dan Non Bank - Sikrillah, Lailatul Sikrillah (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2016)
This study aims to determine the selling price of murabaha financing application and calculation of profit margins on BRISyariah, BPRS Bumi Rinjani and UJKS El-Dinar. The research method used is a qualitative research method with a decriptive approach. Where data is the primary data obtained in the form of interviews with the parties concerned and secondary data in the form of data processing can be acconted for from a reliable source to conduct library research, interviews and internet. The result of this study found that setting the selling price on BRISyariah Murabahah Financing, BPRS Bumi Rinjani and UJKS El-Dinar that use the same basic price plus a profit margin. As for determining the profit margin that the bank sets its own and equally consider five factors determining the margin is the profit margin on everage Islamic Bank (Direct Competitor’s Market Rate/ DCMR), the interest rate the everage conventional banks (indirect Competitor’s Market Rate/ ICMR), the result of third-party funds (Competitive Expected Return for Investor/ ECRI), Overhead Cost, profit targets taking into account inflation and interest rate markets. In a benefit margin calculations using a flat (fixed).